2009
DOI: 10.1210/jc.2008-1284
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Muscle Function in Post-Menarchal Adolescent Girls

Abstract: From these data we conclude that vitamin D was significantly associated with muscle power and force in adolescent girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
181
2
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(197 citation statements)
references
References 29 publications
8
181
2
6
Order By: Relevance
“…Fitness may also be associated with vitamin D concentrations because greater fitness is likely linked to increased outdoor activities (38) and thus exposure to sunlight (6) , as predicted in the present study. It should however also be mentioned that girls (12-14 years) with low s-25(OH)D have been shown to generate less power, jump less height and have lower velocity than girls with higher s-25(OH)D concentrations, measured as the 'Esslinger Fitness Index' which represents efficiency and asymmetry of movement and maximum voluntary force of each leg (39) , suggesting that a lower CRF as a consequence of lower 25(OH)D could be one potential explanation for the positive association between CRF and 25(OH)D. Several studies worldwide have reported higher vitamin D status in boys compared with girls, although the reason is unclear (6)(7)(8) , but these studies were only examining vitamin D status, irrespective of intake. In the present study boys had higher fitness and higher intakes of vitamin D than girls, but there was no gender difference in serum vitamin D status.…”
Section: Discussionmentioning
confidence: 99%
“…Fitness may also be associated with vitamin D concentrations because greater fitness is likely linked to increased outdoor activities (38) and thus exposure to sunlight (6) , as predicted in the present study. It should however also be mentioned that girls (12-14 years) with low s-25(OH)D have been shown to generate less power, jump less height and have lower velocity than girls with higher s-25(OH)D concentrations, measured as the 'Esslinger Fitness Index' which represents efficiency and asymmetry of movement and maximum voluntary force of each leg (39) , suggesting that a lower CRF as a consequence of lower 25(OH)D could be one potential explanation for the positive association between CRF and 25(OH)D. Several studies worldwide have reported higher vitamin D status in boys compared with girls, although the reason is unclear (6)(7)(8) , but these studies were only examining vitamin D status, irrespective of intake. In the present study boys had higher fitness and higher intakes of vitamin D than girls, but there was no gender difference in serum vitamin D status.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, jumping mechanography provides sound clinical evaluation of vitamin D's impact on muscles required for locomotion [35]. Jumping mechanography has also been found to evaluate a broader range of individuals with lesser physical capabilities [140].…”
Section: Assessment Of Muscle Power In Children With Oimentioning
confidence: 99%
“…This relationship has been shown in pre and post menarcheal healthy girls however it has yet to be studied in the OI population [34,35]. Through its effect on muscle size and function, vitamin D plays an important role in acquisition of muscle strength [33].…”
Section: Introductionmentioning
confidence: 98%
“…Also, in young people, a positive relationship between vitamin D status and muscle performance has been reported [2,3]. Given these observations, it is no surprise that 8-12 weeks vitamin D plus calcium supplementation in institutionalized vitamin D-deficient elderly people improved musculoskeletal function by 4-11% [4] and body sway by 9% in ambulatory elderly women [5].…”
Section: Introductionmentioning
confidence: 94%